Affinity Group In EFL Classroom - Juang Kurniawan Syahruzah (Universitas PGRI Yogyakarta, 2020)
The purpose of this research is to know the effect of affinity group in EFL reading classroom of English Department students in University of PGRI Yogyakarta. In measuring the reading comprehension of students the pre-test and post-test are done. The experiment of reading comprehension is done by recruiting of 19 students of EFL reading classroom and do the training and exercising of reading text in reading class. These students are all second-year at PBI-UPY and aged between 17 and 20. Standard measurement is comparison of students answer in pre-test and post-test of reading exercises. The result of this research is students who passed the standard score improved from 25% in the preliminary data to 71% at the end of the research. It means that affinity group strategy improves students’ reading comprehension that is influenced by student’s factors and lecturer factors.